ANALISIS ZAT PEWARNA RHODAMIN B PADA KERUPUK YANG BEREDAR DI KOTA MANADO - Dawile, Sherly; Fatimawali, Fatimawali; Wehantouw, Frenly (PHARMACON, 2013)
ABSTRACTRhodamine B dye in the form of a crystalline powder green or reddish purple, odorless, anddissolves easily in bright red solution berfluoresan as textile dyes. Rhodamine B is still nofood products were found to contain rhodamine B dye such as crackers, sauces, ice and otherpastries. The purpose of this study is to investigate and determine the levels of rhodamine Bon crackers circulating in the city of Manado. Sampling sites crackers are 4 market in the cityof Manado is Tuminting Market, Market Paal 2, Market Market Bersehati 45 and 45.Samples with ammonia to soak interesting rhodamine B dye using wool yarn, followed byidentification using thin layer chromatography (TLC) and then in detection with UV light 254nm and 366 nm. The reading levels of rhodamine B using UV-Vis spectrophotometry. Theresults showed that of the ten samples tested with three times obtained one positive samplecontaining rhodamine B with an average concentration value of rhodamine B in a sample of45 markets in the sword of 0.28 mg/ml. Based on these results, some crackers circulating inManado City Market unsafe consumed.Keywords: Rhodamine B, Crackers, spectrophotometry and Thin Layer Chromatography